Learners' oral corrective feedback preferences in relation to their cultural background, proficiency level and types of error. (October 2016) - Yang, Juan
Abstract: This study examines the preference of adult learners of Chinese as a second language (CSL) for six types of oral corrective feedback (OCF) on phonological, lexical, grammatical, and pragmatic errors in relation to their cultural background and proficiency levels. A sample of 159 university students completed a Likert scale questionnaire and shared their views on how they prefer OCF in a follow-up interview. The results showed learners generally preferred metalinguistic feedback, explicit correction, and recasts on nearly all types of errors. Recasts were viewed as OCF more useful for phonological errors than for lexical and grammatical errors. Intermediate level learners tended to believe that clarification requests on pronunciation errors were effective, whereas beginning level learners did not have the same confidence. Explicit correction on pragmatic errors was viewed as effective by learners from Confucian cultural background; however, learners from non-Confucian background did not agree with this view. A follow-up interview revealed that the linguistic features of learners' first language, cognitive processing, affect, instruction, and cultural perception were five main factors influencing learners' OCF preferences. Implications are suggested for the use of OCF to help understand learners' expectations of CF in second language instruction.